Pengaruh Pengetahuan Dasar Akuntansi, Pengalaman Usaha, dan Modal Usaha Terhadap Keberhasilan Bisnis Startup Digital (Survey Startup di Palembang) - Delia Amanda Putri; Leriza Desitama Anggraini; Reny Aziatul Pebriani (CV. Ulil Albab Corp, 2024)
The research is aimed at testing and analyzing the impact of basic knowledge of accounting, business experience, and enterprise capital on the success of a digital startup business. The study used a quantitative method with a sampel of as many as 50 employees. The data is obtained by using a questionnaire fist, after which validity and realisticity tests are carried out. Data analysis using SPSS (Statistical Product and Service Solutions) involves first performing normality tests and linearity tests, then performing hypothetical testing. The results of the test study showed that the basic knowledge of accounting obtained a thitung value of 6.008 > 2.013 and sig 0.00 < 0.05, which partially positively affected the success of the startup business; the business experience variabel gained thitung values of 8.582 > 2.013 and sig 0.00 < 0.05 that partially affected the startup business success; and the enterprise capital variables gained a thitung value of 5.164 > 2.013 and sig 0.00 < 0.05, which partly positively influenced the successful startup business. As well, the results of the F test showed that simultaneously, basic knowledge of accounting, business experience, and business capital have a positive and significant impact on the success of the startup business (sig. 0.00 < 0.05). This research can provide input that is useful for a company or aagency in making decisions or building for its company so that there are no mistakes in taking decisions.